PENGUATAN LITERASI NUMERIK SISWA SEKOLAH DASAR MELALUI REPRESENTASI DATA PIKTOGRAM DAN DIAGRAM BATANG: KAJIAN LITERATUR - Simatupang, Tetty Aprilya Rezeki; Lumbantobing, Dwi Wulan Joy; Panjaitan, Natasya Ruth Putri; Simbolon, Nadya Tesalonika (Universitas Negeri Medan, 2025)
Improving numeracy skills is an important aspect of mathematics learning in elementary schools. Numeracy encompasses not only arithmetic skills, but also the ability to understand, interpret, and utilize data in visual form. This article discusses the role of pictograms and bar charts as effective visual representation media to help students understand data presentation concepts. The research method used was a literature study reviewing various sources related to literacy, numeracy, and the application of pictograms and bar charts in learning. The results of the study show that the use of these two media can improve data analysis, critical thinking, and problem-solving skills in elementary school students. Pictograms help students understand data concepts concretely, while bar charts strengthen abstract and systematic thinking skills. Previous studies also show that the application of the Problem-Based Learning (PBL) model and PANDITA media (Pictogram and Bar Chart Board) significantly improves student learning outcomes. Thus, the use of contextual and interactive visual representations can be an effective strategy to strengthen numeracy from the elementary education level.